Designing mathematical model and stochastic hybrid random method for a cache system to create a hybrid cache algorithm for web proxy to increase the speed of accessing and processing data: al- Khulaydi, Abd al-Majid Ahmad Ghalib Ali, Mansur Numan Marhub - al- Khulaydi, Abd al-Majid Ahmad Ghalib Ali, Mansur Numan Marhub (مجلة الأندلس للعلوم التطبيقية, 2023)
الملخص EN This scientific article contains a mathematical model design and stochastic hybrid random method design for a cache system to get a hybrid cash algorithm to increase the speed of accessing, processing and saving data.. By this method, we can hybrid any kind of algorithms with each other. The simplicity of this method in hybridization is not only exclusive to web server but can be also used with databases, information systems, operating systems and CPU. Experiments were carried out to measure performance proficiency of hybrid cache algorithms by helping trace-driven simulation by comparing between our hybrid cache algorithm with famous hybrid cache algorithms (LRFU). Our hybrid algorithm contains three algorithms(GDS, LRU ,LFU).Our hybrid algorithm was used in squid proxy that works with operation system Linux . This proxy server checks the data by the famous hybrid algorithm (LRFU) and our hybrid designed algorithm. The results of our hybrid designed algorithm indicate that Hit Ratio (HR) was 22 % and Byte Hit Ratio (BHR) was 18% compared with famous hybrid algorithm (LRFU). This indicates that our hybrid cache designed algorithm is more efficient than famous algorithm (LRFU)